Pelatihan Pengukuran Kinerja Koperasi Sesuai Tujuannya bagi Sarjana Aparatur Sipil Negara (ASN) Kementrian Koperasi dan UKM Angkatan II-Tahun 2023 - Indra, Nurhayat (E-Coops-Day, 2024)
In the last two years, the Ministry of Cooperatives and SMEs has had strategic policies and superior programs, namely the cooperative modernization program with three pillars: institutional modernization, business, and cooperative finance. To realize this program, it needs to be supported by young State Civil Apparatus (ASN) who have strong cooperative competencies. Therefore, through collaboration with the Indonesian Cooperative University LPPM, in 2023 carried out a Basic Cooperative Training Program Batch I and II. This training aimed to improve the cognitive competence, attitudes, and skills of ASN in the cooperative sector. The training method used was competency-based training with adult training methods (andragogy). The results of the training evaluation indicate that this training has been able to provide effective changes in participants' cognitive, attitudes and skills.